A Study of Impacting Factors on Technology Adoption in the Public Sector of Pakistan - Atique, Muhammad; Safeer, Asif Ali; Ullah, Atta; Iftikhar, Huma (The journal of contemporary issues in business and government, 2021)
Social media technology provides different services for the greater benefit of citizens. Like many other developing nations, Pakistan has a low level of social media technology adoption in the public sector. The purpose of this study is to investigate the obstacles and hindrances of the adoption of social media from the public sector's point of view. In this study, a changed variant of the unified theory of acceptance and use of technology (UTAUT) demonstration is utilised to examine the factors impacting the take-up of social media by the public sector in Pakistan. The outcomes demonstrate that the factors affecting the adoption of social media in Pakistan are identified as: usability, value, social impact, innovation issues, lack of proper training and human resource, information security, and trust. Suggestions for online services providing e-organisations and information regarding the government top management approach are likewise considered in this study.